2019
DOI: 10.1186/s13046-019-1188-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA AGAP2-AS1, functioning as a competitive endogenous RNA, upregulates ANXA11 expression by sponging miR-16-5p and promotes proliferation and metastasis in hepatocellular carcinoma

Abstract: Background Accumulating evidence has highlighted the potential role of long non-coding RNAs (lncRNAs) in the biological behaviors of hepatocellular carcinoma (HCC). Here, we elucidated the function and possible molecular mechanisms of the effect of lncRNA-AGAP2-AS1 on the biological behaviors of HCC. Methods EdU, Transwell and flow cytometry were used to determine proliferation, migration, invasion and apoptosis of HCC cells in vitro. The subcutaneous tumor model and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 34 publications
2
71
0
Order By: Relevance
“…LncRNA SBF2-AS1 acts as a ceRNA to affect acute myeloid leukemia cell proliferation through sponging with miR-188-5p [22]. LncRNA AGAP2-AS1, functioning as a ceRNA, up-regulates the expression of ANXA11 via binding with miR-16-5p and promotes cell proliferation and metastasis in hepatocellular carcinoma [23]. In our analysis, we discovered that DSCAM-AS1 bound with miR-877-5p and DSCAM-AS1 modulated the expression of miR-877-5p in a negative manner in CC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA SBF2-AS1 acts as a ceRNA to affect acute myeloid leukemia cell proliferation through sponging with miR-188-5p [22]. LncRNA AGAP2-AS1, functioning as a ceRNA, up-regulates the expression of ANXA11 via binding with miR-16-5p and promotes cell proliferation and metastasis in hepatocellular carcinoma [23]. In our analysis, we discovered that DSCAM-AS1 bound with miR-877-5p and DSCAM-AS1 modulated the expression of miR-877-5p in a negative manner in CC.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA LUCAT1 has been indicated to promote proliferation and invasion in ccRCC cells via the AKT/GSK-3β signaling pathway (20). lncRNA AGAP2-AS1 ectopic expression has been indicated in numerous types of carcinoma, including in hepatocellular carcinoma (14), non-small cell lung cancer (9,10), gastric cancer (15) and glioma (11). Furthermore, AGAP2-AS1 has been indicated to be co-expressed with HDGF (21) and ANGPTL4 (13), which are associated with tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, AGAP2-AS1 was indicated to be associated with highly metastatic tumor characters by recruiting zeste homolog 2 (13). Additionally, further studies have revealed that the upregulated expression of AGAP2-AS1 markedly correlates with clinical features in hepatocellular carcinoma (HCC) and promotes the effects of hypoxia on metastasis and EMT (14). AGAP2-AS1 has also been detected in tissues samples of patients with gastric cancer and gastric cancer cell lines, which suggests that AGAP2-AS1 may be a potential prognostic biomarker (15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lncRNAs are known to affect disease progression by serving as molecular ceRNA sponges that can sequester miRNAs [38]. For example, one group found that the lncRNA AGAP2-AS1 plays a competitive role in hepatocellular carcinoma via acting as a miR-16-5p sponge [39]. In present study, we searched for potential upstream regulators of miR-6979-5p using the LncBase Experimental V.2 Database (http://carolina.imis.athena-innovation.gr/ diana_tools/web/index.php?r=lncbasev2%2Findex-e xperimental), leading to our identification of the lncRNA Rhno1.…”
Section: Discussionmentioning
confidence: 99%